Media Pembelajaran Metaverse Sebagai Tujuan Meningkatkan Kualitas Pendidikan - M A Rizky Aditya N; Rizki Wijayanto; Bugito Danuarta; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
This research aims to elucidate the design of metaverse learning media with the goal of improving the quality of education. Metaverse is a virtual environment that enables interaction among users through 3D avatar representations. In the context of education, the use of metaverse offers a different learning experience, optimizing the current technology and educational media, and supporting the development of soft skills and building confidence through the simulations offered. This research also discusses the potential and limitations of metaverse educational applications, as well as the challenges and opportunities for their use in the education world. The research findings indicate that the use of metaverse in education can overcome existing limitations, such as classroom capacity, distance, and time constraints. However, the use of metaverse also poses some challenges, such as user security and privacy. Therefore, the design of metaverse learning media needs to consider these aspects to enhance the quality of education.